A simple label-free photoelectrochemical immunosensor for highly sensitive detection of aflatoxin B1 based on CdS–Fe3O4 magnetic nanocomposites. Issue 25 (21st March 2015) - Liu, Yixin; Yan, Tao; Li, Yueyun; Cao, Wei; Pang, Xuehui; Wu, Dan; Wei, Qin
<x xml:space="preserve">Abstract</x> A simple label-free photoelectrochemical (PEC) platform was developed based on magnetic CdS–Fe3O4 nanocomposites and used for detection of aflatoxin B1 (AFB1).